ANALSISI FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT BPK RI PERWAKILAN PROVINSI JAWA TIMUR - Megawati, Shofia (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aimns to analyze the effect of long relationships between auditors and auditees, pressure from the auditee, knowledge, and experience on audit quality. The study uses 69 respondents as samples who are auditors of The Audit Board of Republic of Indonesia (BPK RI) East Java Province Representative. The research hypotheses are tested using the multiple regression analysis. Work on data analysis techniques, using SPSS 15.0 for windows. The result show that long-standing relationship between auditors and auditees, knowledge, and experience has positive effect on audity quality; while pressure from the auditees affects audit quality negatively.Keywords: Audit Quality, Relationship between Auditor and Auditee, Pressure from Auditee, Knowledge, Experience.